THE STRATEGIC ANALYSIS OF DOMESTIC AVIATION ENGINE-BUILDING ON THE BASIS OF A MATRIX OF THE BOSTON CONSULTING GROUP - N. Zemlyanskaya; N. Kazakova; A. Sazonov (Вестник университета)
In article questions of the analysis of engine-building corporation through use of a matrix of Boston consulting group are taken up. The decisions assumed by BCG design depend on the provision of a concrete type of business of corporation in the strategic space formed by two coordinate axes. On ordinate axis value of growth rates of the market is postponed.